Day 1 Tue, August 11, 2015 2015
DOI: 10.2118/174641-ms
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Modelling of Alkaline/Surfactant/ Polymer Flooding Process at Under-Optimum Salinity Condition for Enhanced Oil Recovery

Abstract: Alkaline-Surfactant-Polymer (ASP) flooding is potentially the most efficient chemical EOR methods. It yields extremely high incremental recovery factors in excess of 95% of residual oil for water flooding. The current opinion is that such extremely high recoveries can only be achieved at optimum salinity conditions, i.e. for the Winsor type III micro-emulsion phase characterized by an ultra-low interfacial tension (IFT). This represents a serious limitation since several factors including alkali-rock interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…It is suggested that, for reservoirs with weak heterogeneity, EOR should focus on enhancing oil displacement efficiency; for reservoirs with strong heterogeneity, EOR should be based on improving sweep efficiency. Hosseini-Nasab et al 116 used numerical simulation, which proved that the surfactant prepared with low-salinity water has less adsorption retention than the surfactant prepared with the optimal salinity, and produced 66% of the surfactant. However, only 15% of the surfactant can be produced above the optimum salinity.…”
Section: Application Of In Situ Emulsification In the Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…It is suggested that, for reservoirs with weak heterogeneity, EOR should focus on enhancing oil displacement efficiency; for reservoirs with strong heterogeneity, EOR should be based on improving sweep efficiency. Hosseini-Nasab et al 116 used numerical simulation, which proved that the surfactant prepared with low-salinity water has less adsorption retention than the surfactant prepared with the optimal salinity, and produced 66% of the surfactant. However, only 15% of the surfactant can be produced above the optimum salinity.…”
Section: Application Of In Situ Emulsification In the Fieldmentioning
confidence: 99%
“…Hosseini-Nasab et al used numerical simulation, which proved that the surfactant prepared with low-salinity water has less adsorption retention than the surfactant prepared with the optimal salinity, and produced 66% of the surfactant. However, only 15% of the surfactant can be produced above the optimum salinity.…”
Section: Application Of In Situ Emulsification In the Fieldmentioning
confidence: 99%
“…After Winsor’s pioneering work, ,, oil/water phase behavior tests, and their evaluations, have been the major focus of surfactant formulation development and selection before core flood tests. The IFT values between oil and aqueous phases are usually estimated based on the phase behavior results, including water and oil solubilization, and surfactant structure, or are not reported. Usually, determining reliable IFT values in a robust way is a challenge, mainly due to time effects on the IFT and the effects of multicomponent nature of the surfactant, the oil, and the brine.…”
Section: Introductionmentioning
confidence: 99%